Abundance Moina sp. Given The Mixed Fish Meal, Soybean Meal and Bran With Different Concentration - Febriyanto, Andi; Hasibuan, Saberina; Pamukas, Niken Ayu (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted on June to July 2016 in BPBAT Jambi. The purpose of this studi to determine the abundance of Moina sp. in artificial media with different concentrations of organic matter. The method used by the experimental method completely randomized (RAL) with four treatments and three replications. Treatment with giving fish meal, soy meal and bran as media results show the highest abundance population Moina sp. and the best gift weir Giving fish meal (0.15 g) + soy meal (0.15g) + bran (0.3g) with an average abundance of 403 ind/L. Water quality during the study showed a good range for growth Moina sp. namely pH 7.01 - 8.29, Dissolved Oxygen 4.21 - 6.80 mg/L, the water temperature from 26.9 - 28.9 Â°C and NH3 of 0.023 - 0.21 mg/L.Keyword: Moina sp. phytoplankton and organic materials